An amino acid-derived ABCBA-type antifouling biohybrid with multi-stimuli responsivity and contaminant removal capability. Issue 14 (17th March 2022) - Kumar, Devendra; Mohammad, Sk Arif; Kumar, Anand; Mane, Shivshankar R.; Banerjee, Sanjib
Abstract : We report a multi-stimuli (pH/thermo/redox) responsive (PCysMAM- b -PDMAEMA- b -PB- b -PDMAEMA- b -PCysMAM) pentablock copolymer biohybrid which exhibits antifouling property and contaminant removal capability. Abstract : Multi-stimuli (pH/thermo/redox)-responsive amphiphilic poly(cysteine methacrylamide)- block -poly(2-(dimethylamino)ethyl methacrylate)- block -polybutadiene- block -poly(2-(dimethylamino)ethyl methacrylate)- block -poly(cysteine methacrylamide) (PCysMAM- b -PDMAEMA- b -PB- b -PDMAEMA- b -PCysMAM) pentablock copolymer biohybrids, based on hydrophobic PB, ampholytic redox responsive PCysMAM and dual (pH and temperature) stimuli responsive PDMAEMA segments, are synthesized via a four-step synthesis protocol. The synthesis protocol involves: (1) in situ post polymerization modification of living polybutadiene-based carbanionic species to prepare hydroxyl terminated polybutadiene (HTPB); (2) introduction of an initiating functionality (capable of acting as an ATRP initiator) to HTPB, yielding a telechelic ATRP macroinitiator (Br-PB-Br); (3) recyclable alloy-mediated successive RDRP of DMAEMA and CysMAM, yielding a series of PCysMAM- b -PDMAEMA- b -PB- b -PDMAEMA- b -PCysMAM (A-B-C-B-A) pentablock copolymers with various chain lengths; and (4) conversion of the PDMAEMA block to poly(quaternary ammonium) (PQA) via quaternization. The stimuli responsiveness of the copolymer is investigated against changes in pH, temperature and redox. The pentablock copolymer self-assembles into spherical nanospheres, can switch between its monocationic, zwitterionic and monoanionic charged states, exhibits antifouling behaviour and is capable of removing ionic contaminants from water. These pentablock copolymers may emerge as a promising material for emerging applications.